What’s your poison?: identifying Pb ingestion and its effects from the Neolithic to modern day - Fear, Catrin (2025)
“The past is key to assessing the nature and scale of our impacts today” (Boivin and Crowther 2021: 273) Over the last two decades, archaeological studies have examined lead pollution levels in stratified environmental archives from the Neolithic onwards, to understand the past impacts of human activities. Lead is a trace metal whose natural cycles have been heavily affected by anthropogenic activities. As a result, lead pollution has been used to trace anthropogenic activities, and to understand the onset of the Anthropocene. However, lead is also present in human skeletal remains, and is a time-transgressive archive reflecting contaminant exposure (López-Costas et al. 2020). This thesis has examined the development and impact of lead on human populations across the last two millennia, producing the first assessment of the historic uptake of lead pollution by the human population across Britain. From this, a date-range for the onset of the Anthropocene has been suggested, based on the point at which lead in the human population reaches concerning levels. This thesis is the first to use lead from a human bioarchaeological perspective to question what is currently considered a ‘safe’ Blood Lead Level (BLL), as well as the ratios for understanding BLL in archaeological remains.